3k-6+2k=12+8k-33

Simple and best practice solution for 3k-6+2k=12+8k-33 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3k-6+2k=12+8k-33 equation:


Simplifying
3k + -6 + 2k = 12 + 8k + -33

Reorder the terms:
-6 + 3k + 2k = 12 + 8k + -33

Combine like terms: 3k + 2k = 5k
-6 + 5k = 12 + 8k + -33

Reorder the terms:
-6 + 5k = 12 + -33 + 8k

Combine like terms: 12 + -33 = -21
-6 + 5k = -21 + 8k

Solving
-6 + 5k = -21 + 8k

Solving for variable 'k'.

Move all terms containing k to the left, all other terms to the right.

Add '-8k' to each side of the equation.
-6 + 5k + -8k = -21 + 8k + -8k

Combine like terms: 5k + -8k = -3k
-6 + -3k = -21 + 8k + -8k

Combine like terms: 8k + -8k = 0
-6 + -3k = -21 + 0
-6 + -3k = -21

Add '6' to each side of the equation.
-6 + 6 + -3k = -21 + 6

Combine like terms: -6 + 6 = 0
0 + -3k = -21 + 6
-3k = -21 + 6

Combine like terms: -21 + 6 = -15
-3k = -15

Divide each side by '-3'.
k = 5

Simplifying
k = 5

See similar equations:

| -4x-18=-(4x+2) | | 3/2+3/4 | | 8+4y=12 | | 65x=55x+100 | | m-14/9=-27 | | 4k+11+2k=-5-27k-3 | | 4x+16=4(x+4) | | 11/2+3/4 | | 3=-6n-9 | | 3(4-x)-22=x+48 | | 99x^8+63x^5-45x^2= | | -3+4(-6y-2)=4(2y-1)+3 | | y-10=-1(x-4) | | -25y+25y=-(22y+15)+10+22 | | 3x-10=5x+14 | | -33k=19 | | B+(-11)=6 | | x/3+7=11 | | -2*(-8)+4y=-8 | | -12(m-4)=240 | | -2m+8=4 | | -1v-6= | | 3x(4x+5)-5(4x+5)=0 | | (5x-2)-(6-2X)=-x-9+5x | | 4-(-72/18) | | 0.5/n=2.5/4.5 | | 2x-2/4+3=6 | | y^2-y= | | 3x*x+18x+23=2x*x+12x+14 | | -5/6a=5/8 | | 5x+4=8x-2 | | 8+x-5=12 |

Equations solver categories